1993
DOI: 10.1007/bf00311625
|View full text |Cite
|
Sign up to set email alerts
|

A case report of gastric cancer associated with sarcoid reactions in the regional lymph nodes and liver

Abstract: Epithelioid cell granulomas identical to those of systemic sarcoidosis are occasionally observed within malignant neoplasms, particularly in the lymphatics draining a primary tumor. These histologic changes have been termed sarcoid reactions and are easily confused with systemic sarcoidosis. This report describes an extremely rare case of gastric cancer accompanied by sarcoid reactions in the regional lymph nodes and liver parenchyma near a tumor metastasis. A 63-year-old woman with advanced gastric cancer was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…6,8,9,13-15,21,23,33,45-56 , 5,7,10-12,16-20,22,24,25,27-32,34-44,59 Most often, these reactions are observed in lymph nodes draining the malignancy but can also occur in distant organs or the tumor-affected organ itself. [5][6][7][10][11][12][16][17][18][19][20]22,24,25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]46,47,59 The mechanism for sarcoidlike reactions remains unknown. 46 Some authors have suggested a T-cell-mediated host response to soluble tumor antigens and others a reaction to tumor cell metabolites.…”
mentioning
confidence: 99%
“…6,8,9,13-15,21,23,33,45-56 , 5,7,10-12,16-20,22,24,25,27-32,34-44,59 Most often, these reactions are observed in lymph nodes draining the malignancy but can also occur in distant organs or the tumor-affected organ itself. [5][6][7][10][11][12][16][17][18][19][20]22,24,25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]46,47,59 The mechanism for sarcoidlike reactions remains unknown. 46 Some authors have suggested a T-cell-mediated host response to soluble tumor antigens and others a reaction to tumor cell metabolites.…”
mentioning
confidence: 99%
“…To the best of our knowledge, 20 cases of gastric cancer associated with sarcoid-like reactions have had their clinical, surgical, and pathological findings documented in detail; [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] ours was the twenty-first case report. In 15 [21][22][23][24]26,[28][29][30][31]33,34,[36][37][38] of the 21 patients, intraabdominal lymphadenopathy was detected during surgery. And, in 11 21,22,[28][29][30]33,34,[36][37][38] of the 15 patients, this was regarded as tumor metastasis because of the abnormal firmness of lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…In 15 [21][22][23][24]26,[28][29][30][31]33,34,[36][37][38] of the 21 patients, intraabdominal lymphadenopathy was detected during surgery. And, in 11 21,22,[28][29][30]33,34,[36][37][38] of the 15 patients, this was regarded as tumor metastasis because of the abnormal firmness of lymph nodes. Namely, lymph nodes with the sarcoidlike reaction associated with gastric cancer were often enlarged and firm, and signaled tumor metastasis in the lymph node.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Granulomatous reactions occurring within lymph nodes draining carcinomas are a well-known but uncommon occurrence [1,2,3]. These histologic changes have been termed sarcoid reactions, and such changes have been described in association with lymphoma and other solid tumors [4,5,6,7,8,9]. However, the presence of this response in colorectal cancer has been considered to be quite rare, and only a few reports have mentioned the presence of granulomatous reactions in colorectal cancer [10,11,12].…”
Section: Introductionmentioning
confidence: 99%